The Interplay Between Beta-Amyloid 1–42 (Aβ1–42)-Induced Hippocampal Inflammatory Response, p-tau, Vascular Pathology, and Their Synergistic Contributions to Neuronal Death and Behavioral Deficits - Calvo-Flores Guzmán, Beatriz; Elizabeth Chaffey, Tessa; Hansika Palpagama, Thulani; Waters, Sarah; Boix, Jordi; Tate, Warren Perry; Peppercorn, Katie; Dragunow, Michael; Waldvogel, Henry John; Faull, Richard Lewis Maxwell; Kwakowsky, Andrea (Frontiers in Molecular Neuroscience, 2020)
Alzheimer’s disease (AD), the most common chronic neurodegenerative disorder, has complex neuropathology. The principal neuropathological hallmarks of the disease are the deposition of extracellular beta-amyloid (Aβ) plaques and neurofibrillary tangles (NFTs) comprised of hyperphosphorylated tau (p-tau) protein. These changes occur with neuroinflammation, a compromised blood-brain barrier (BBB) integrity and neuronal synaptic dysfunction, all of which ultimately lead to neuronal cell loss and cognitive deficits in AD. Aβ1-42 was stereotaxically administered bilaterally into the CA1 region of the hippocampi of 18-month-old male C57BL/6 mice. This study aimed to characterize utilizing immunohistochemistry and behavioral testing the spatial and temporal effects of Aβ1-42 on a broad set of parameters characteristic of AD: tau, neuroinflammation, vascular pathology, pyramidal cell survival, and on behavior. Three days after Aβ1-42 injection and before significant neuronal cell loss was detected, acute neuroinflammatory and vascular responses were observed, as shown by the up-regulation of both glial fibrillary acidic protein (GFAP) and cell adhesion molecule-1 (PECAM-1, also known as CD31), fibrinogen labeling, and an increased number or activated astrocytes and microglia in the CA1 region of the hippocampus. From day 7, there was significant pyramidal cell loss in the CA1 region of the hippocampus, and by 30 days, significant localized up-regulation of p-tau, GFAP, Iba-1, CD31 and alpha-smooth muscle actin (α-SMA) in the Aβ1-42-injected mice compared with controls. These molecular changes in Aβ1-42-injected mice were accompanied by cognitive deterioration, as demonstrated by long-term spatial memory impairment. This study is reporting a comprehensive examination of a complex set of parameters associated with intrahippocampal administration of Aβ1-42 in mice and their spatiotemporal interactions and combined contribution to the disease progression. We show that a single Aβ injection can reproduce aspects of the inflammatory, vascular and p-tau induced pathology occurring in the AD human brain that lead to cognitive deficits.